Electric power supply structure transformation model of China for peaking carbon dioxide emissions and achieving carbon neutrality - Shengyuan Liu; Yicheng Jiang; Shuyang Yu; Weitao Tan; Tianhan Zhang; Zhenzhi Lin (Energy Reports, 2022)
As the largest developing country in the world, China has promised to peak the carbon dioxide emissions before 2030 and achieve carbon neutrality before 2060 to mitigate the greenhouse effect. In the meantime, the electric power industry is playing a key role in achieving this ambitious target through “electricity substitution” and “clean substitution” strategies and constructing the “new type of power system”. Given this background, a specific and detailed model for the electric power supply structure transformation (EPSST) model is proposed in this rapid communication for the first time, which helps to analyse the transformation more reasonably. The proposed EPSST model aims to minimize the total costs for electric power supply structure transformation with the carbon neutrality constraints considered. Besides, the other constraints associated with the construction and retirement of different types of power plants, the balance between power supply and demand, and carbon sinks are also considered. Two scenarios aiming to achieve carbon neutrality before 2060 and 2055 are respectively studied and corresponding analyses for the transformation are also performed. The results show the feasibility of the proposed EPSST model and finally a macroscopic forecast for the future electric power industry is given.